Multicultural Learning Strategies to Improve Social Care Character at an Elementary School: A Case Study at Muhammadiyah 6 Elementary School North Samarinda - Agus Salim, Nur; Adianto, Samsul; A’yuni, Qurrotul (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2023)
This study aims to analyze teacher strategies in shaping social care character and constraints experienced in shaping social care character of third grade students at Muhammadiyah 6 Elementary School North Samarinda 2022/2023 Academic Year. This study uses qualitative methods with data collection techniques namely interviews, observations, and documentation. The study conducted at SD Muhammadiyah 6 Samarinda Utara revealed creative strategies adopted by teachers to cultivate social care character among third grade students. By implementing routine activities such as ‘Sharing Friday’, weekly infaq, and spontaneous responses in the form of reprimands and advice, teachers inculcate caring values. They also demonstrate exemplary behavior and transform the classroom environment to facilitate better social interactions. The use of magic words in daily interactions and the integration of social care values in Civics Education lessons emphasize the importance of empathy and solidarity. The researcher recommends that the school develop learning materials that reflect the cultural, religious and ethnic diversity in Indonesia and provide professional training for teachers on how to integrate multicultural education into their teaching and how to identify and respond to bias in the classroom.